(NmR)QÆÃMO Z lESE@ uKRAÇNKO@ (B:s)E (NL)QÆT(B. (NROZWAGA DLQ DÆTEJ ST(B. (NGRUPI (B/s)E - (NkOWALENKO(B, (Na(B.,s (2017)
(NsCENAR)QÆJ(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NuKRA)QÇNKA l(B.s)E; (NmETODIKA NAW^ANNQ W DO[K)QÆLXNIH NAW^ALXNIH ZAKLADAHs)E -- (NUKRA)QÇNSXKA LÆTERATURAs)E -- (NuKRA)QÇNAs)E; (NdO[K)QÆLXNE WIHOWANNQs)E -- (NESTETI^NE WIHOWANNQs -- (NZASOBAMI L)QÆTERATURIs)E -- (NuKRA)QÇNAs)E; (NDO[K)QÆLXNÆ NAW^ALXNÆ ZAKLADIs)E; (NMETODIKA NAW^ANNQs; (NUKRA)QÇNSXKA LÆTERATURAs)E; (NSCENAR)QÆJs)E; (NL)QÆTERATURNÆ SWQTAs)E; (NL)QÆTERATURNÆ ROZWAGIs)E; (NPOETI^N)QÆ TWORIs)E; (NTEATRAL)QÆZACÆQs)E; (NSTAR[IJ DO[K)QÆLXNIJ WÆKs)E; (NESTETI^NE WIHOWANNQs